Ballooning‐Interchange Instability in the Near‐Earth Plasma Sheet and Auroral Beads: Global Magnetospheric Modeling at the Limit of the MHD Approximation. Issue 14 (14th July 2020) - Sorathia, K. A.; Merkin, V. G.; Panov, E. V.; Zhang, B.; Lyon, J. G.; Garretson, J.; Ukhorskiy, A. Y.; Ohtani, S.; Sitnov, M.; Wiltberger, M.
Abstract: Explosive magnetotail activity has long been understood in the context of its auroral manifestations. While global models have been used to interpret and understand many magnetospheric processes, the temporal and spatial scales of some auroral forms have been inaccessible to global modeling creating a gulf between observational and theoretical studies of these phenomena. We present here an important step toward bridging this gulf using a newly developed global magnetosphere‐ionosphere model with resolution capturing ≲ 30 km azimuthal scales in the auroral zone. In a global magnetohydrodynamic (MHD) simulation of the growth phase of a synthetic substorm, we find the self‐consistent formation and destabilization of localized magnetic field minima in the near‐Earth magnetotail. We demonstrate that this destabilization is due to ballooning‐interchange instability which drives earthward entropy bubbles with embedded magnetic fronts. Finally, we show that these bubbles create localized field‐aligned current structures that manifest in the ionosphere with properties matching observed auroral beads. Plain Language Summary: The aurora has long been used as a window onto the magnetosphere. However, auroral observations are inherently limited in trying to reconstruct global magnetospheric dynamics from the "magnetic shadow" they cast on Earth. For this reason modeling has been used in tandem with observations to better contextualize and understand the data. Substorms, the violent reconfiguration of the magnetotail and one of the most dynamic magnetospheric phenomena, have been known to be preceded by the formation of bead‐like structures in the aurora. The processes responsible for auroral beading and their causal versus correlative role with substorm onset have remained an enduring mystery. The vast disparity between the spatial scales of auroral beads and those of the global magnetosphere has greatly complicated the use of modeling in unraveling this mystery. We show here for the first time a demonstration of the self‐consistent formation of a magnetospheric configuration that becomes unstable during the period preceding the substorm onset and that this instability manifests in the ionosphere with similar morphology to auroral beads. The global context of the model shows that the magnetospheric processes responsible for beading are not necessarily causal to onset but a consequence of the slow magnetotail reconfiguration that precedes onset. Key Points: We present the first global magnetosphere simulation to reveal ballooning‐interchange instability of a narrow B z minimum in the near‐Earth magnetotail The instability is prominent during the substorm growth phase and generates earthward entropy bubbles with embedded magnetic fronts The bubbles drive mesoscale ionospheric field‐aligned currents and auroral structures (beads) with properties matching to those observed